2014 16th European Conference on Power Electronics and Applications 2014
DOI: 10.1109/epe.2014.6910819
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the switching frequency on the DC-side admittance in three-phase converter systems

Abstract: Three-phase converter systems can be prone to negative impedance instability of the DC-bus. This paper studies the dynamic interactions between the DC-and AC-sides of a current-controlled three-phase system in order to reveal possible risks of instability. The system is modelled by using a small-signal method from a viewpoint of the DC-side. Time delays due to pre-calculation and discretization are considered. The stability analyses are performed for the small-signal model. The results of the stability analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Option 1 has been typically adopted in works such as [11], [12]. However, it can be shown that G 1 , as well as G 2 , are unstable if VSC 2 acts as a dc load, while G 3 is unstable for P 20 = 0.…”
Section: A Selection Of Subsystemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Option 1 has been typically adopted in works such as [11], [12]. However, it can be shown that G 1 , as well as G 2 , are unstable if VSC 2 acts as a dc load, while G 3 is unstable for P 20 = 0.…”
Section: A Selection Of Subsystemsmentioning
confidence: 99%
“…However, it indicates that there is a risk of instability. To determine if the system is unstable, Nyquist stability criterion can be applied in the SISO system as in [11], [12]. From (27) and Fig.…”
Section: B Passivity Analysis Of the Siso Systemmentioning
confidence: 99%
See 3 more Smart Citations